2010
DOI: 10.1159/000279308
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Metastasis from Renal Cell Carcinoma

Abstract: A 73-year-old female was operated with radical nephrectomy and cholecystectomy for renal cell carcinoma and suspected gallstones after 9 courses of sunitinib treatment. Gallbladder specimen showed gallbladder metastasis originating from the renal cell carcinoma. Gallbladder metastasis from renal cell carcinoma is rare. Here, we discuss a case of gallbladder metastasis from renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…1,2 Its rarity and clinical similarity to benign gallbladder diseases can make correct diagnosis difficult in a clinical situation.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Its rarity and clinical similarity to benign gallbladder diseases can make correct diagnosis difficult in a clinical situation.…”
Section: Introductionmentioning
confidence: 99%
“…Metastatic renal cell carcinoma of the gallbladder has also been described in some case reports [35]. The typical diagnostic sequence begins with the detection of a polypoid lesion by routine ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of the gallbladder is rare (as few as 0.4-0.6% of cases). 6 A review from the US in 2012 by Chung et al found only 33 cases in the published literature. 5 The median time for metachronous metastases was 4 years as opposed to the 14 years in our case.…”
Section: Discussionmentioning
confidence: 99%